Genetic diversity among maize (Zea mays) inbred lines for methionine and yield associated traits - DEVI, VEENA; SETHI, MEHAK; KAUR, CHARANJEET; RAIGAR, OM PRAKASH; KUMAR, RAMESH; CHAUDHARY, DHARAM PAUL (The Indian Journal of Agricultural Sciences, 2024)
A study was carried out during winter (rabi) and rainy (kharif) seasons of 2020–21 at the research farm of ICAR-Indian Institute of Maize Research, Ludhiana, Punjab in which 22 maize inbred lines with varying content of methionine were evaluated to study various seeds and field parameters, and methionine content and further statistically analysed through genetic variability, principal components and hierarchical cluster analysis. Significant differences were noted among inbred lines for various traits. Broad- sense heritability analysis showed that traits exhibited more than 80% heritability, except plant height, cob height and no. of cobs. Principal component analysis showed five principal components having eigen value more than 1.00 and accounted for 82.01% of total variation. Cluster analysis distributed the inbred lines in 4 major clusters suggesting their use in breeding programmes. Correlation analysis was also studied to understand the correlation of field and yield parameters with methionine content. Plant height and cob height (0.83), no. of rows per cob and no. of seeds per row (0.76), anthesis and silking interval (0.89), specific gravity and silking interval (0.45) showed significant positive correlation. Traits including methionine, moisture, 100-kernel weight, no. of cobs, no. of rows/cob, no. of seeds/row and germination rate having higher genotypic and phenotypic coefficient of variation, heritability, and genetic advance mean can be used for further crop improvement programme.